Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Asli Daerah Di Provinsi Yogyakarta Tahun 2010-2015 - Khotijah, Siti; , Siti Fatimah N, SE, MSi (2017)
This study entitled "Analisys of Factors That Affect Local revenues In Yogyakarta Province in 2010-2015". It"s purposed to analyze effect regional gross domestic product,population and investment about local revenue in Yogyakarta province 2010-2015. Dependent variable is local revenue while independent variabel is regional gross domestic product,population and investment. This study uses secondaru data with panel data regression analysis technique. The result showed that the fixed effect model (FEM) is a panel data regression model is most appropriate. Based on test validity or the effect of the t test, regional gross domestic product,population and investment significant positive effect on local revenue. Based on F test, regional gross domestic product,population and investment simultaneously or jointly affect the local revenue. Adjusted R-square 0,9700, or 97%, which mean is 97% variable variation of the local revenue can be explained by regional gross domestic product,population and investment and the rest of 3% variabel variation of the local revenue is explained byother variable not included in the model.